Partners in showcasing history: Activating the land-grant engagement mission through collaborative exhibits. Issue 1 (April 2019) - Bahde, Anne; Edmunson-Morton, Tiah; Fernández, Natalia
The land-grant university in the United States holds a special role in higher education, enacting the ideals of public education, scientific research and direct engagement with the citizens of the state. In this article, three curators from a land-grant university discuss how their exhibit curation work fulfills these ideals through three case studies on exhibit collaborations. By examining lessons learned from their collaborations with students and faculty, campus organizations and community groups, the authors offer suggestions for navigating exhibit partnerships and planning for future collaborations.